Math, asked by aneesshreen298, 1 year ago

If y = \sqrt{\log x + \sqrt{\log x + \sqrt{\log x + ....\infty }}}, show that \frac{dy}{dx} =  \frac{1}{x(2y-1)}

Answers

Answered by Anonymous
0
hey mate
here's the solution
Attachments:
Answered by sk940178
0

Answer:

\dfrac{dy}{dx} = \dfrac {1}{x(2y - 1)}

Step-by-step explanation:

Given:

y = \sqrt{logx + {\sqrt{logx+ \sqrt{logx + \sqrt{logx + ...... \infty}}}}}\\\\y = \sqrt{logx + y} \\\\y^2 = logx + y........ (1)

Now differentiate the equation (1)

2y\dfrac{dy}{dx}= \dfrac 1x + \dfrac{dy}{dx} \\\\ 2y\dfrac{dy}{dx} - \dfrac{dy}{dx}= \dfrac 1x\\\\\dfrac{dy}{dx}(2y - 1)= \dfrac 1x\\\\\dfrac{dy}{dx} = \dfrac {1}{x(2y - 1)}

\dfrac{dy}{dx} = \dfrac {1}{x(2y - 1)}

Hence Proved.

Similar questions